2014
DOI: 10.1103/physrevb.89.144405
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic antidot to dot crossover in Co and Py nanopatterned thin films

Abstract: The crossover from antidot to dot magnetic behavior on arrays patterned in a ferromagnetic thin film has been achieved by modifying only the geometry. A series of antidot arrays has been fabricated on cobalt with fixed diameter d and by reducing the period of the array p from p d to p < d. A dramatic change in the coercivity dependence with p, correlated with a significant modification in the magnetic domain structure observed by x-ray photoemission electron microscopy, evidences the crossover. An intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
43
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 36 publications
10
43
0
1
Order By: Relevance
“…This pattern is consistently repeated around every antidot studied. It is interesting to note that a similar effect has been previously reported on FIB etched antidots and shown to be a local film alteration due to the tail of the Gaussian-like section of the ion beam [18]. However, significant hysteresis is observed, in conjunction to the non-epitaxial polycrystalline structure of the films; in the past it has been shown that vacuum deposited polycrystalline Co films have hcp crystallites, not completely randomly oriented, that induce an in-plane uniaxial anisotropy [22].…”
Section: Sample Morphologysupporting
confidence: 76%
See 1 more Smart Citation
“…This pattern is consistently repeated around every antidot studied. It is interesting to note that a similar effect has been previously reported on FIB etched antidots and shown to be a local film alteration due to the tail of the Gaussian-like section of the ion beam [18]. However, significant hysteresis is observed, in conjunction to the non-epitaxial polycrystalline structure of the films; in the past it has been shown that vacuum deposited polycrystalline Co films have hcp crystallites, not completely randomly oriented, that induce an in-plane uniaxial anisotropy [22].…”
Section: Sample Morphologysupporting
confidence: 76%
“…However, there are significant inherent drawbacks in all of the self-assembly fabrication methods, mainly regarding the limitations of the array symmetry and/ or size and the extent of the symmetric domains, which is on the order of some μm. Only recently advanced fabrication techniques have been introduced for the study of nm-scale antidot arrays, as for example the use of focused ion beam (FIB) patterning [18], which allow for obtaining antidot arrays of any symmetry extending over areas of several tens of μm or even mm.…”
Section: Introductionmentioning
confidence: 99%
“…Both magnetization reversal and anisotropy symmetry for samples 1, 2, and 4 are qualitatively similar to that of sample 3. Interestingly, our results show that due to the large size of the antidots, the qualitative coercivity behavior is very similar for all the antidot samples [17,32]. The peak in the coercivity plot along the hard axis is due to grain orientation disorder [33] which arises due to the non-epitaxial behavior of the film.…”
Section: Methodsmentioning
confidence: 53%
“…В качестве подложки использованы темплаты анодиро-ванного Al 2 O 3 с различной морфологией поверхности, обусловленной размером формируемых пор d p и их количеством в одной ячейке, что может влиять на эффект пиннинга и величину H C наносимого на них материала [20,21].…”
Section: Introductionunclassified